Gene × Environment Interactions in Autism Spectrum Disorders: Role of Epigenetic Mechanisms - Tordjman, Sylvie; Somogyi, Eszter; Coulon, Nathalie; Kermarrec, Solenn; Cohen, David; Bronsard, Guillaume; Bonnot, Olivier; Weismann-Arcache, Catherine; Botbol, Michel; Lauth, Bertrand; Ginchat, Vincent; Roubertoux, Pierre; et al. (Frontiers in Psychiatry, 2014)
Several studies support currently the hypothesis that autism etiology is based on a polygenic and epistatic model. However, despite advances in epidemiological, molecular and clinical genetics, the genetic risk factors remain difficult to identify, with the exception of a few chromosomal disorders and several single gene disorders associated with an increased risk for autism. Furthermore, several studies suggest a role of environmental factors in autism spectrum disorders (ASD). First, arguments for a genetic contribution to autism, based on updated family and twin studies, are examined. Second, a review of possible prenatal, perinatal and postnatal environmental risk factors for ASD are presented. Then, the hypotheses are discussed concerning the underlying mechanisms related to a role of environmental factors in the development of ASD in association with genetic factors. In particular, epigenetics as a candidate biological mechanism for gene X environment interactions is considered and the possible role of epigenetic mechanisms reported in genetic disorders associated with ASD is discussed. Furthermore, the example of in utero exposure to valproate provides a good illustration of epigenetic mechanisms involved in ASD and innovative therapeutic strategies. Epigenetic remodeling by environmental factors opens new perspectives for a better understanding, prevention and early therapeutic intervention of ASD.